Application of Solenoid Valves for Tram Hydraulic Braking Force Control - ZHANG Yanwei; MAO Jinglu; WANG Cong; WANG Zhongxiang; HAO Xinxin (Chengshi guidao jiaotong yanjiu)
［Objective］ The control solenoid valves in the hydraulic braking system of trams mainly include proportional pressure reducing valve and high-speed switching valve. Due to the structural characteristics, the former is poor in pollution resistance and has high failure rate. While the latter is presently only used by Knorr-Bremse, and few domestic manufacturers are involved in it. It is necessary to compare the two types of control solenoid valves application in the control of hydraulic braking force, evaluate their structures, working principles, and closed-loop control performance, so as to provide references for the design of the tram hydraulic braking force control system. ［Method］ The structures and working principles of the two types of solenoid valves for hydraulic braking force control, namely proportional pressure reducing valve and high-speed switching valves, are introduced. The hydraulic braking force control principle based on the two types of valves are elaborated in detail. A test bench for the tram hydraulic braking force control is set up, and pressure following tests with 0.5 Hz and 1.0 Hz sinusoidal waves are carried out on the two types of valves respectively by using closed-loop control algorithms. The following situations of the actual pressure curves and the target pressure curves are compared. ［Result & Conclusion］ The hydraulic braking system based on the working principle of high-speed switching valve has a high precision of closed-loop control for braking force, and is applicable to fully automatic operation lines that require precise control and automatic calibration of braking force. This valve has fast response to braking force control and outstanding anti-slip ability, conductive to reducing the risk of wheel abrasion. Compared with proportional pressure reducing valve, the high-speed switching valve features strong pollution resistance, which can lower the failure rate of the braking system. Therefore, the hydraulic braking system based on the principle of high-speed switching valve is worthy of being popularized and applied in the field of hydraulic braking technology for trams.